Biophysical investigation into the antibacterial action of modelin-5-NH2. Issue 20 (10th May 2019) - Dennison, Sarah R.; Hauß, Thomas; Badiani, Kamal; Harris, Frederick; Phoenix, David A.
Abstract : Neutron diffraction studies showed that modelin-5-CONH2 has potent antibacterial activity which involves membrane interactive, tilted α-helical structure. Abstract : Modelin-5-CONH2 (M5-NH2 ) is a synthetic antimicrobial peptide, which was found to show potent activity against Bacillus subtilis (minimum lethal concentration = 8.47 μM) and to bind strongly to membranes of the organism ( K d = 10.44 μM). The peptide adopted high levels of amphiphilic α-helical structure in the presence of these membranes (>50%), which led to high levels of insertion (Δ π ≥ 8.0 mN m −1 ). M5-NH2 showed high affinity for anionic lipid ( K d = 7.46 μM) and zwitterionic lipid ( K d = 14.7 μM), which drove insertion into membranes formed from these lipids (Δ π = 11.5 and 3.5 mN m −1, respectively). Neutron diffraction studies showed that M5-NH2 inserted into B. subtilis membranes with its N-terminal residue, L16, located 5.5 Å from the membrane centre, in the acyl chain region of these membranes, and promoted a reduction in membrane thickness of circa 1.8 Å or 5% of membrane width. Insertion into B. subtilis membranes by the peptide also promoted other effects associated with membrane thinning, including increases in membrane surface area ( C s −1 decreases) and fluidity (Δ G mix > 0 to Δ G mix < 0). Membrane insertion and thinning by M5-NH2 induced high levels of lysis (>55%), and it is speculated that the antibacterial action of the peptide may involve the toroidal pore, carpet or tilted-type mechanism of membrane permeabilization.